Some reactions of perfluoroglutaric acid - Smith, D. A. (College of Aeronautics, 1964)
Perfluoroglutaric acid when reacted with methyl magnesium iodide affords 2,6 diol 2,6 dimethyl hexafluoro pyranI in high yield and 4-one, 1,2,3 hexafluoro caproic II acid in low yield. The former material appears to exist in a range-melting form (64-79°C) and a very labile form of melting point 96-98°C. The 2,6 diol 2,6 dimethyl hexafluoro pyranI yields a mono semi carbazoneIII, and also a monoIV and a di 2:4 dinitro phenyl hydrazone. V The mono 2:1l dinitrophenyl hydrazone appears to be cyclic. Reduction both with lithium aluminium hydride and sodium borohydride yields 2,6 diol 3,4,5 hexafluoro n-heptane.VI There is evidence to suggest that reaction with dried calcium sulphate gives 2 ene, 2 methyl 3,4,5 hexafluor 6 one cyclo-hexaneVII Reaction with benzoyl chloride affords 2,6 dibenzoate, 2,6 dimethyl hexafluoro pyran.VIII 4 one 1,2,3, hexafluorocaproic acid was characterised as a 2:4 dinitro phenyl hydrazoneIX and also as an S benzyl thio-uranium salt.X Infra-red spectral evidence suggests the S benzyl thio uranium salt probably exists in the straight chain form. Numbers in the above text refer to the Flow Sheet, Figure 1.